ANALISIS KUALITAS PELAYANAN PUBLIK DI KANTOR CAMAT SANGKULIRANG KABUPATEN KUTAI TIMUR - Marjoni Rachman Aisyah (ADMINISTRASI PUBLIK, 2017)
This research aims to know and describe the quality of public services in the Office of East Kutai Regency Camat Sangkulirang. The approach used in this research is descriptive qualitative approach. This will be done in the research description of the five indicators of the quality of public services, namely Tangibles, Reliability, Responsiveness, Assurance and Emphaty.The results showed that the Quality of Public Service held in Sangkulirang Sub-district Office of East Kutai Regency was 69.2% and this was in the interval of 56% - 75% or included in good enough category. Thus the formulation of the problem in this study has been well answered.